Dilemmas of pluralist democracy : autonomy vs. control - Dahl, Robert A., 1915-2014. (New Haven : Yale University Press, 1982)
Annotation Like individuals, then, organizations ought to possess some autonomy, and at the same time they should also be controlled. Crudely stated, this is the fundamental problem of pluralist democracy. The purpose in this book is to explore the problem of pluralist democracy and some possible solutions.
Future urban America : post-affluent or advanced industrial society? / Gary Gappert -- Part I. Urban changes : what pattern is this place? -- The evolving dynamics of American urban development / James F. Richardson -- City development in advanced industrial societies / Richard V. Knight -- Seven scenarios of urban changes / Arthur Shostak -- Part II. Demographic relaties : is demography destiny? -- Urban growth in the sunbelt / Kathleen Butler and Ben Chinitz -- The Hispanic-American urban order : a border perspective / Warner Bloomberg and Rodrigo Martinez-Sandoval -- The future of black ghettos / Harold M. Rose -- Part III. Forces of transformation : will cities enjoy the future? -- New city types in an energy-short world / Jon Van Til -- Middle managers go on strike : a report from 2001 / Larry Hirschhorn -- New technologies and their urban impact / Joseph F. Coates -- Toward the androgynous city / Susan Saegert -- Irregular economies / John P. Blair -- Part IV. Forces of intertia : will urban changes ever change? -- The future of urban neighborhoods / David J. O'Brien and Lynn Clough -- Enduring elements of urban design and architecture / Richard Fleischman -- Frontierism and civil leadership / Frank Costa and Yong Cho -- The future of urban danger / Sally Engle Merry -- Part V. Policies of transition : can cities manage their transformation? -- The future of fiscal federalism / James Alm and Jesse Burkhead -- Changes in the provision of public services / Deborah Bickford and Charles Vehorn -- Epilogue. Urban management and the future / Gary Gappert and Richard V. Knight.
Includes bibliographical references (pages 211-217) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Democracy; Cultural pluralism; Associations, institutions, etc; Public interest; Cultural Diversity; Societies; Diversité culturelle; Associations; Intérêt public; public interest; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Associations, institutions, etc; Cultural pluralism; Democracy; Public interest; Electronic book